Chinatown and Monster Homes: The Splintered Chinese Diaspora in Vancouver - Madokoro, Laura (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2011)
This article offers a critique of the cohesiveness and solidarity implied in many studies of diaspora by exploring the role of historical memory as a disruptive force in the local sites of the diasporic experience. The focus of the article is on a series of controversial housing and development debates in Vancouver from the 1960s to the 1980s, all of which involved groups of Chinese Canadians or recent Chinese immigrants. Through archival research and interviews, the controversy over the construction of “monster homes” by Chinese investors and immigrants in the late 1980s is shown to be completely divorced from the solidarity generated within the Chinese community in Vancouver a generation earlier as a result campaigns to save the residential neighbourhood of Strathcona and the adjacent commercial Chinatown area. The article concludes that the absence of shared memories in a local space undermines the potential for political mobilization within a diasporic community.